Association of Foveal Avascular Zone Diameter with Best-Corrected Visual Acuity in Diabetic Retinopathy: A Cross-Sectional Optical Coherence Tomography Angiography Study - Ramzi Amin; Rezandi Pratama; Petty Purwanita; Muhammad Aulia Molid Ogest Putra Calisanie (HM Publisher, 2026)
Background: Foveal avascular zone (FAZ) enlargement reflects capillary loss in diabetic retinopathy (DR), but its relationship with visual acuity varies across protocols and populations. Objective: We assessed the association between swept-source optical coherence tomography angiography (OCTA)-derived FAZ diameter and best-corrected visual acuity (BCVA). Methods: This cross-sectional study included 32 adults with DR examined from April to December 2024. One eye per participant underwent 3×3-mm swept-source OCTA. Superficial and deep FAZ diameter, superficial vessel density, central subfield thickness, and LogMAR BCVA were assessed using correlations, severity-group comparisons, multivariable regression, and exploratory secondary analyses. Results: Mean age was 57.8±8.4 years; 17 participants (53.1%) were men. Mean superficial FAZ diameter was 617.6±171.6 µm and BCVA was 0.539±0.341 LogMAR. FAZ diameter correlated with worse BCVA (r=0.582, 95% confidence interval [CI] 0.293–0.774; p<0.001) and increased from 458.3±82.1 µm in mild nonproliferative DR to 812.5±125.8 µm in proliferative DR (F(3,28)=16.35; p<0.001; η²=0.637). FAZ was the largest standardized correlate in the exploratory adjusted model (β=0.485; p<0.001; adjusted R²=0.412). An exploratory 580-µm cutoff yielded an area under the curve of 0.847 (95% CI 0.723–0.971). Conclusion: Larger superficial FAZ diameter was associated with worse BCVA and greater DR severity. The proposed cutoff and secondary models require independent validation.